Methodological aspects of research of neopaganism (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes theformation and development ofneo-paganismasa phenomenon ofcultural-religious lifein today’ssociety.The authors explores thephilosophical,religious,socio-political, historical andcultural aspects of the phenomenon. Tracing the genetic links between neo-paganism and archaic, author emphasizes nonequivalence of these concepts and reveals their difference. Analyzes the socio-psychological and cultural-ideological reasons of the growth needsin neo-paganism in today’s society.Analyzing the phenomenon of neo-paganism in the modern social-humanities sciences the author does not consider this phenomenon as a clearly negative.In the knowledgeandunderstandingof ethno-cultural identityit canplay a positive role. However, one-sidedly interpreted with the political positions, neo-paganism may have a negative impact on the public consciousness and social behavior that may generate negative processes in the social and spiritual sphere.Key words: Religion, religious relations,neo-paganism,archaic, consciousness, unrecognized,archetype, «Pop-religion».